Alginate microencapsulation for oral immunisation of finfish: release characteristics, ex vivo intestinal uptake and in vivo administration in Atlantic salmon, Salmo salar L - Bikramjit Ghosh; Barbara Nowak; Andrew Bridle (2015)
This study examined the feasibility of alginate microcapsules manufactured using a low-impact technology and reagents to protect orally delivered immunogens for use as immunoprophylactics for fish. Physical characteristics and protein release kinetics of the microcapsules were examined at different pH and temperature levels using a microencapsulated model protein, bovine serum albumin (BSA). Impact of the microencapsulation process on contents was determined by analysing change in bioactivity of microencapsulated lysozyme. Feasibility of the method for oral immunoprophylaxis of finfish was assessed using FITC-labelled microcapsules. These were applied to distal intestinal explants of Atlantic salmon ( Salmo salar ) to investigate uptake ex vivo. Systemic distribution of microcapsules was investigated by oral administration of FITC-labelled microcapsules to Atlantic salmon fry by incorporating into feed. The microcapsules produced were structurally robust and retained surface integrity, with a modal size distribution of 250–750 nm and a tendency to aggregate. Entrapment efficiency of microencapsulation was 51.2 % for BSA and 43.2 % in the case of lysozyme. Microcapsules demonstrated controlled release of protein, which increased with increasing pH or temperature, and the process had no significant negative effect on bioactivity of lysozyme. Uptake of fluorescent-labelled microcapsules was clearly demonstrated by intestinal explants over a 24-h period. Evidence of microcapsules was found in the intestine, spleen, kidney and liver of fry following oral administration. Amenability of the microcapsules to intestinal uptake and distribution reinforced the strong potential for use of this microencapsulation method in oral immunoprophylaxis of finfish using sensitive immunogenic substances.